PERTUMBUHAN IMAN DAN PEMBENTUKAN GAYA HIDUP PEMUDA GKN GLORIA YOGYAKARTA MELALUI LOVE COMMUNITY - Nevi Try Kasih Daeli; Eka Setyaadi; Andreas Jonathan (JURNAL PENABIBLOS, 2024)
Christian youth are often highlighted for their lifestyle, one of which is the youth of GKN Gloria. In GKN Gloria, youth have a different lifestyle, outside the church, youth smoke, drinkalcohol, wear revealing clothes. Other things do not grow in faith because they still live in sin. The church provides Love Community, however, it is ineffective due to the absence of guidance material for coaching. This study aims to determine the factors that cause youth to have different lifestyles and the factors that cause them not to grow in faith. The method used is qualitative descriptive. The findings are that there are differences in lifestyle caused by the residential environment, the desire to enjoy life by living freely, fear of being ostracized and bullied; the cause of not growing is because of falling and rising in sin and not doing spiritual discipline. Based on the problems above, Love Community can be made effective, and the researcher proposes six spiritual coaching guidelines to realize the growth of faith and a lifestyle with integrity.